2015
DOI: 10.1097/aci.0000000000000202
|View full text |Cite
|
Sign up to set email alerts
|

Corneal complications of vernal keratoconjunctivitis

Abstract: Corneal complications in VKC are the result of an on-going process of uncontrolled inflammation. Proper recognition of the corneal complications in VKC is crucial, as most of these can be managed or prevented by a combination of medical and surgical measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 23 publications
0
35
0
1
Order By: Relevance
“…[ 10 11 ] VKC is a chronic allergic disease affecting tarsal conjunctiva and limbus. [ 12 13 ] It is an IgE-mediated hypersensitivity reaction where binding of allergen-specific IgE to high-affinity IgE receptors on mast cells releases histamines and other cytokines causing inflammation. [ 12 ] Histamine is a mediator of itch response,[ 5 ] which triggers eye rubbing leading to KC progression by increasing protease activity.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 11 ] VKC is a chronic allergic disease affecting tarsal conjunctiva and limbus. [ 12 13 ] It is an IgE-mediated hypersensitivity reaction where binding of allergen-specific IgE to high-affinity IgE receptors on mast cells releases histamines and other cytokines causing inflammation. [ 12 ] Histamine is a mediator of itch response,[ 5 ] which triggers eye rubbing leading to KC progression by increasing protease activity.…”
Section: Discussionmentioning
confidence: 99%
“…Routine corneal topography in patients with VKC allows early detection and management of subclinical and clinical keratoconus. [7][8][9] Gautam and his friends conducted a study on VKC patients in Nepal. 28.7% of patients was diagnosed with palpebral, 14.8% of patients was diagnosed with limbal and 56.5% of patients was diagnosed with mixed VKC.…”
Section: Discussionmentioning
confidence: 99%
“…It has been showed that chronic epithelial defects result in changes in corneal topography by causing long term and slight oscillation in destructive enzymes. 3,[7][8][9] The studies conducted in previous years have shown the relation between keratoconus and VKC with clinical analysis. [9][10][11] Yet, with these methods, it cannot be proven the relationship between VKC and keratoconus in the patients with subclinical keratoconus.…”
mentioning
confidence: 99%
“…[29] Corneal complications appear to be one of the earliest causes of visual impairment and can cause permanent decrease or loss of vision in children. [30] Vision screening alone, although recommended in primary school children, will not identify VKC cases. Therefore, incorporating eye examinations into the routine vision screening is recommended.…”
Section: Discussionmentioning
confidence: 99%